Pengaruh Penggunaan Media Pembelajaran Non-Digital "Jadul" terhadap Konsentrasi Siswa saat Belajar Mata Pelajaran PAI - Fadilah Ramadhani Br. Ginting; Rizka Harfiani (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2025)
This study aims to analyze the influence of using non-digital or “traditional” learning media on the learning concentration of Grade X students in Islamic Religious Education (PAI). The background of this research is based on the phenomenon of increasing student distractions caused by the use of gadgets and digital media, which often reduce focus during the learning process. Therefore, alternative learning strategies are needed by utilizing simple media that emphasize direct interaction between teachers and students. The research method used is quantitative with a survey approach through questionnaires distributed to Grade X students as respondents. The study population consists of all Grade X students at one senior high school, with the sample determined using Slovin’s formula to ensure representativeness. Data were analyzed using simple regression techniques to measure the extent of the influence of non-digital learning media on students’ concentration levels in PAI learning. The results of the study show a positive and significant effect, where non-digital learning media such as blackboards, flashcards, and simple teaching aids were proven to help increase focus, reduce distractions, and strengthen comprehension of religious subject matter. In addition, the use of traditional media encourages active student participation through discussions and hands-on activities, making the learning process more interactive. Thus, this study concludes that non-digital learning media remain relevant as effective alternatives, particularly in PAI learning for Grade X students, and can serve as a practical solution in addressing the challenges of the digital era, which is filled with potential distractions.